FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS DENGAN TATA KELOLA PERUSAHAAN YANG BAIK SEBAGAI VARIABEL MODERAT PADA BANK PEMBANGUNAN DAERAH - Anhar, Febri; Abdurrahman, Abdurrahman; Bertuah, Eka; Jumono, Sapto (UNIVERSITAS KARIMUN, 2024)
This research aims to determine the role of credit risk, liquidity and capital adequacy ratio on profitability moderated by Good Corporate Governance at Regional Development Banks in Indonesia for 2017 - 2022. Data obtained from the annual financial reports of Regional Development Banks and using 23 Regional Development Banks with a total sample 184 banks. Data collection used the purposive sampling method, and the data analysis used was Moderated Regression Analysis (MRA). Data analysis management uses Eviews 13.0 software. This test uses hypothesis testing in the form of the F and t-tests. Apart from that, classical assumption tests are also used in the form of normality tests, multicollinearity tests, autocorrelation tests and heteroscedasticity tests. The results of this research indicate that credit risk has a negative effect on profitability, liquidity and capital adequacy do not affect profitability and good corporate governance can strengthen the relationship between the influence of credit risk, liquidity and capital adequacy on profitability.